2017
DOI: 10.1186/s40494-017-0153-2
|View full text |Cite
|
Sign up to set email alerts
|

The artists’ materials of P. S. Krøyer: An analytical study of the artist’s paintings and tube colours by Raman, SEM–EDS and HPLC

Abstract: An analytical study of two paintings by P. S. Krøyer and the tube colours found in his painting cabinet has been carried out in order to investigate the artists' materials used by Krøyer in the latter part of his oeuvre. The study has given a valuable knowledge about Krøyer's choice of materials and their composition that may be helpful in e.g. preservation issues. The pigments and dyes were analysed by micro-Raman spectroscopy (MRS), scanning electron microscopyenergy dispersive X-ray spectroscopy (SEM-EDS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…The red specimen is interesting in that it is the only one that shows evidence of an organic additive, which could be either a varnish or an adhesive binder, such as, typically, a pine resin. Likewise remarkable are the absence of other strong pigments from his palette and favoured by many of his contemporaries [53,54] such as ultramarine, basic lead white (hydrocerussite), orpiment, azurite, malachite, and weaker but more common ones such as goethite and verdigris. The admixture of red lead and hematite in the red pigment is also rather curious and was intended obviously for a particular tonal shade.…”
Section: Discussionmentioning
confidence: 96%
“…The red specimen is interesting in that it is the only one that shows evidence of an organic additive, which could be either a varnish or an adhesive binder, such as, typically, a pine resin. Likewise remarkable are the absence of other strong pigments from his palette and favoured by many of his contemporaries [53,54] such as ultramarine, basic lead white (hydrocerussite), orpiment, azurite, malachite, and weaker but more common ones such as goethite and verdigris. The admixture of red lead and hematite in the red pigment is also rather curious and was intended obviously for a particular tonal shade.…”
Section: Discussionmentioning
confidence: 96%
“…4 c. However, in the optical microscope image, the fluorescent particles are indistinguishable from the rest of the components of the ground. Therefore, a white pigment with fluorescence characteristics 24 , such as zinc white, must have been used in the preparation of the ground layer 43 . The average diameter calculated for those particles was 5 m. The evidence that zinc white may be present includes its cold, flat tone 34 , poor oil drying and low pigment density 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Even more recently, Christiansen et al studied paint tubes and two paintings by P.S. Krøyer (1851-1909), which lent insight into the materials chosen by this Danish artist in the last part of his career [33]. This work relied on micro-Raman, SEM-EDX and HPLC, and in a subsequent study that focussed on the pigment in the tube labelled as "Jaune de Cadmium Citron" [34], they found that this contained a rare cadmium chromate compound (KCd 2 (CrO 4 ) 2 (H 3 O 2 )).…”
Section: Previous Technical Studies On Oil Paint Tubesmentioning
confidence: 99%